(untitled) (Altre Modernità, 2022)
This paper proposes an analysis of the storytelling of the COVID pandemic in Wuhan in the first months of 2020 as depicted by two TV dramas: Heroes and With you. This analysis will be carried out by identifying the elements common to the two TV series in the description of their protagonists and the way in which they dialogue with real people and about real facts, also in relation to the presentations offered by television producers to the press, and those published in specialized or party magazines. The dramas are therefore considered as spaces of interpretation of the individual experience in a collective sense, and as discourses in which memory exerts a fundamental role in the definition of the social and cultural self, in order to understand whether the COVID pandemic is regarded in China as a cultural trauma.